Exploration of synthesis of anthocyanins in passion fruit pericarp through combinatorial transcriptomic analysis and WGCNA - Chen, Hui-Ying; Gao, Fan-Li; Guo, Quan; Bao, Sheng-Nan; Li, Xia; Khoo, Hock Eng (Frontiers in Plant Science, 2025)
Passion fruit (Passiflora edulis) is extensively cultivated in most tropical and subtropical regions worldwide. Yet although its pulp, well known for nutritional profile, is commonly processed into juice and other products, the peel remains underutilized, leading to substantial biomass wastes. This study investigates the molecular mechanisms of anthocyanin accumulation in the peel through the integrative transcriptome and WGCNA analysis. Samples were collected at both mature and immature developmental stages from purple- and yellow-skinned passion fruit varieties. Transcriptome sequencing was performed on the Illumina-Hiseq platform. After stringent quality trimming and filtering, the clean reads were aligned to the reference genome. Differentially expressed genes (DEGs) were identified using DESeq2 with the thresholds of |log2Fold Change| ≥ 1 and FDR < 0.05. To elucidate their biological functions and metabolic pathways, the DEGs were annotated against the KEGG, GO and KOG databases. Subsequent WGCNA,pinpointed ten candidate hub genes potentially involved in anthocyanin biosynthesis. Finally, their expression patterns were validated via RT-qPCR, which showed strong concordance with the transcriptome data. These findings not only confirm the robustness of our analytical approach but also highlight the pivotal regulatory roles of several key genes, involving PeCA, PeMYC2, PeMYB88, and PeCHI, in the passion fruit anthocyanin biosynthesis pathway.